Let the Games Begin - Jensen, Lars Taagaard; Iversen, Evald (Forum for Idræt, 2007)
Artiklen har fokus på lovgningsprocesserne af den tidligere og nuværende eliteidrætslov, i perioderne 1979-1984 og 2002-2004. Evald Iversen and Lasse Taagaard Jensen: Let the Games Begin – the elite sports laws of 1984 and 2002 This article tries to develop an understanding of the interplay between the Danish Government (i.e. the Ministry of Culture) and the interest organisations within the area of elite sports. The central argument is that close cooperation exists between the actors in the field. The Government as well as the interest organisations possess resources that are interesting seen from their counterparts perspective. On the basis of the first elite sports law the elite sports organisation »Team Danmark« was created in 1984. Its success and the contentment from athletes at the elite level meant that Team Danmark was difficult to ignore when a second elite sport law was in the making in 2004. The organisation had marked itself as a new player in field of elite sports. The Minister of Culture and the Chairman of the National Olympic Committee and Sports Confederation of Denmark (Danmarks Idræts Forbund) had a firm association during the process which led to the newest legislation in 2004 – but eventually they could not control the legislation process. This was partly due to the other players involved and partly to these partners cooperation with the media. In the end this meant that the 2004 process became fragmented with several actors involved – even though the interplay between the state and the sports organisations continued to be intertwined with relatively few actors involved.